Technological Characterization of Clay and Chamotte Incorporated in Handmade Ceramics - Dayana Rosy Souza dos Santos; Oscar Jesus Choque Fernandez; Diogo Monteiro Porfírio; Marison Franco Rocha de Lima; Ramon Sousa dos Santos; Patrícia Magalhães Pereira Silva (Materials Research)
The municipality of Bragança, Pará, Brazil, is renowned for its artisanal ceramic production, where chamotte is reused as a substitute for clay materials. In this study, test specimens were formulated and produced with clay partially replaced by chamotte in proportions ranging from 0% to 25%, and sintered between 600°C to 1000°C. Both the clay and chamotte underwent technological characterization. The specimens were subjected to physical and mechanical analyses. The raw materials consist of quartz, illite, kaolinite, and K-feldspar, with SiO2 and Al2O3 as the predominant chemical components. The clay is clayed silt, exhibits an appropriate plasticity index, and undergoes structural transformations as the temperature increases, confirming its suitability for ceramic applications. The best results were obtained with 5% to 15% chamotte in ceramics sintered at 900°C, reaching a mechanical strength of 7 MPa. The data on various technological properties indicate the feasibility of producing artisanal ceramics incorporating chamotte.